Inhibition of neutrophil elastase prevents neutrophil extracellular trap formation and rescues mice from endotoxic shock. (April 2020) - Okeke, Emeka B.; Louttit, Cameron; Fry, Chris; Najafabadi, Alireza Hassani; Han, Kai; Nemzek, Jean; Moon, James J.
Abstract: Neutrophil elastase (NE) is a serine protease stored in the azurophilic granules of neutrophils and released into the extracellular milieu during inflammatory response or formation of neutrophil extracellular traps (NETs). Neutrophils release NETs to entrap pathogens by externalizing their cellular contents in a DNA framework decorated with anti-microbials and proteases, including NE. Importantly, excess NETs in tissues are implicated in numerous pathologies, including sepsis, rheumatoid arthritis, vasculitis, and cancer. However, it remains unknown how to effectively prevent NET formation. Here, we show that NE plays a major role during NET formation and that inhibition of NE is a promising approach for decreasing NET-mediated tissue injury. NE promoted NET formation by human neutrophils. Whereas sivelestat, a small molecule inhibitor of NE, inhibited the formation of NETs in vitro, administration of free sivelestat did not have any efficacy in a murine model of lipopolysaccharide-induced endotoxic shock. To improve the efficacy of sivelestat in vivo, we have developed a nanoparticle system for delivering sivelestat. We demonstrate that nanoparticle-mediated delivery of sivelestat effectively inhibited NET formation, decreased the clinical signs of lung injury, reduced NE and other proinflammatory cytokines in serum, and rescued animals against endotoxic shock. Collectively, our data demonstrates that NE signaling can initiate NET formation and that nanoparticle-mediated inhibition of NE improves drug efficacy for preventing NET formation.